Early cistercian polyphony: a newly-discovered source - Ferreira, Manuel Pedro (2011)
This paper presents a two-voice hymn to St. Bernard, found by the author in the Arouca Monastery. This hitherto unpublished hymn, which can be dated around 1225, is the most ancient polyphonic work found so far in Portugal, and one of the oldest examples of polyphony copied in Cistercian manuscripts. To explain its presence in Arouca, the author examines both the local and the international context; the problem of polyphonic practice in the Cistercian Order receives special attention, and several related compositions are transcribed. The musical style of the hymn is then discussed and its peculiar, conservative character put into relief against the background of European polyphonic practice. The interpretative transcription offered is then justified at length.